Exploring Perspectives on Adolescent Mental Health Services Across Continents: A Literature Review - Nurannisa, Fitri Revita; Anggreni, Miranda Chrisan; Rusprayunita, Nurendah Ratri A; Citraningtyas, Veriana Indah (BKM Public Health and Community Medicine, 2024)
Background: The prevalence of mental health issues among adolescents worldwide necessitates thorough investigation, as these conditions significantly diminish the quality of life and impose substantial burdens on the economy, education, and overall well-being. The originality of our research lies in its compilation and analysis of reports from countries representing both low- and middle-income countries (LMICs) and high-income countries (HICs). This approach provides a broader insight into the mental health conditions among adolescents and offers recommendations tailored to their specific needs. Purpose: This study aims to analyze the effectiveness of adolescents' mental health services and identify the obstacles they overlook regarding their mental states. Method: This literature study is based on several mental health-related survey reports from representatives across four continents: Indonesia, Ireland, Germany, Kenya, Vietnam, and Australia. We retrieve all reports and resources from online databases such as PubMed, Google Scholar, and ScienceDirect. We further analyze these reports and compile them with studies that meet our inclusion criteria. Result: Among all the reports analyzed, Australia has the highest coverage of mental health service utilization by adolescents. All reports demonstrate that adolescents typically seek help from family members or close friends. Additionally, the reports indicate that government mental health programs are not yet inclusive and are scarcely accessible to youth, possibly due to scheduling issues, geographical barriers, unclear procedures, and other factors. Conclusion: The utilization of mental health services among adolescents remains inadequate. More youth-friendly and inclusive policies are needed. Additionally, the involvement of parents and peers is crucial to maximizing the effectiveness of these interventions.